2020
DOI: 10.1080/16742834.2020.1738208
|View full text |Cite
|
Sign up to set email alerts
|

Dry deposition of ammonia around paddy fields in the subtropical hilly area in southern China

Abstract: This study measured the ammonia (NH 3 ) concentration and dry deposition within 100 m around paddy fields (0.6 ha) with double rice cropping in the subtropical hilly area in southern China, with the aims to quantify the dry deposition of NH 3 around the emission source and to clarify its temporal and spatial variability. The results showed that high NH 3 concentrations were found during the 15 d after nitrogen (N) fertilizer application at downwind sites within 100 m around the paddy fields, and the NH 3 conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Mitigation of atmospheric ammonia pollution can be achieved not only by decreasing emissions from sources, but also by increasing ammonia deposition around sources. Yi et al (2020) found that 80% of the emitted ammonia was dry deposited within 100 m of the studied paddy fields (0.6 ha) in the subtropical hilly regions of China. Thus, not all volatilized ammonia can enter the atmosphere to form aerosols.…”
Section: Impacts and Mitigation Of Atmospheric Reactive Nitrogenmentioning
confidence: 90%
“…Mitigation of atmospheric ammonia pollution can be achieved not only by decreasing emissions from sources, but also by increasing ammonia deposition around sources. Yi et al (2020) found that 80% of the emitted ammonia was dry deposited within 100 m of the studied paddy fields (0.6 ha) in the subtropical hilly regions of China. Thus, not all volatilized ammonia can enter the atmosphere to form aerosols.…”
Section: Impacts and Mitigation Of Atmospheric Reactive Nitrogenmentioning
confidence: 90%
“…The complex interactivity between cloud feedback and aerosol-clouds may affect temperatures and humidity in orchards, which can be beneficial to the dispersal of viruses into plants mediated by plant transpiration ( 75 ). Furthermore, nitrogen deposition induces eutrophication and neutralizes the pH of the water, including groundwater and that in escape canals in the limestone mountains, which could increase the risk of microbial aggregation through bridging bacteria ( 74 , 76 ). Due to the lack of nutrition data required by different plants at different growth stages in different climatic regions and the absence of biosensors, even intelligent water and fertilizer integration facilities often cause excessive water and fertilizer irrigation.…”
Section: Discussionmentioning
confidence: 99%